1968
DOI: 10.1017/s0003356100026350
|View full text |Cite
|
Sign up to set email alerts
|

A note on effect of exercise on behaviour and performance of confined swine

Abstract: The effects of exercise on food intake, growth rate and behaviour were investigated in two trials with 32 pigs. The exercise took the form of running or walking four times the length of a concrete path twice a day. Food intake and rate of gain in body weight were decreased by exercise; the thickness of back fat was not significantly affected. Exercise increased the amount of time spent resting. It is concluded that exercise does not appear to be a practical method of producing leaner carcasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Our results demonstrated that the Bi-LSTM model accurately predicted sow estrus with an 86% accuracy rate within the ground-truth region. Our findings were in line with the previous research [12], which noted that sows tend to stand or sit for longer periods during estrus. his suggests that CCTV footage can be effectively used to predict sow estrus, and by collecting more data and adjusting the ground-truth region, we can achieve greater accuracy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated that the Bi-LSTM model accurately predicted sow estrus with an 86% accuracy rate within the ground-truth region. Our findings were in line with the previous research [12], which noted that sows tend to stand or sit for longer periods during estrus. his suggests that CCTV footage can be effectively used to predict sow estrus, and by collecting more data and adjusting the ground-truth region, we can achieve greater accuracy.…”
Section: Discussionsupporting
confidence: 93%
“…As ovulation approaches, sows tend to search for boars more frequently. Another study [12] found that sows housed individually in stalls tend to stand or sit for longer periods compared with non-estrus periods because of their limited movement.…”
Section: A Sow Behavior and Estrusmentioning
confidence: 99%
“…It is possible that the behavioural changes caused by the hot treatment (see Results) may have contributed to the increase in backfat depth caused by the hot treatment, although any effect would probably have been small Cunningham, 1964 andMorrison, Hintz and Givens, 1968). Although from the very limited results presented in this paper there was no evidence of changes in the thyroid or adrenal glands caused by the hot treatment, it is possible that these did occur (Ingram and Slebodzinski, 1965;Collins and Weiner, 1968) and that these contributed to the increased backfat depth caused by the hot treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Morrison, Hintz and Givens (1968) were unable to demonstrate an effect of exercise on the carcass composition of growing pigs. Morrison, Hintz and Givens (1968) were unable to demonstrate an effect of exercise on the carcass composition of growing pigs.…”
Section: Discussionmentioning
confidence: 88%